LOW COST APPROXIMATE ADDER SUBTRACTOR FOR FIR FILTER - W.A. Mahmou; Dhafer R. Zagha; Mohannad K. Sabir (Journal of Engineering, 2003)
The cost of the FIR filter depends on the cost of its components that are classified into three types namely buffer, multiplier and adder/subtractor.The adder/subtractor cover the most FIF. rilter components and any reduction in its cost means high reduction in the total cost of FIR filter. tn addition, FIR filters with pipeline multiplier the speed of FIR depends on the speed of adder/subtractor and any improvement in speed will result to increasing in the total speed of such filter.This paper shows a proposed method to increase the speed and reduce the cost of the adder/subtractor by neglecting the rotated carry output. This method reduces the accuracy of FIR filter, in other words it adds small noise to the output of the filter, but the level of this noise is inversely proportional with the number of bits in data bus of FIR filter. Therefore this method will be used with midum noise output filters or with wide data bus (12-bits or more) FIR filter.